Palm-based oils as milk fat alternatives in Mozzarella cheese analogue - Ismail, N.H.; Mat Yusoff, M.; Mohd Hassim, N.A.; Saw, M.H.; Wazir, H.; Tang, T.K.; Kanagaratnam, S. (Consejo Superior de Investigaciones Cientificas, 2024)
This research featured the noteworthy properties of a Mozzarella cheese analogue composed of palm oil (PO) and palm olein (POo) as milk fat alternatives. The objective of this study was to examine the properties of a palm-based Mozzarella cheese analogue (P-MCA) in comparison to a fat-free Mozzarella cheese analogue (FF-MCA) and a commercial Mozzarella cheese sample (CMC) containing 68% palm-based Mozzarella cheese analogue. Mozzarella cheese samples were analyzed for compositional properties, color, functional properties (stretchability and meltability) and sensory evaluation. The stretchability and meltability of both P-MCA and FF-MCA were desirably and significantly (p < 0.05) higher than the C-MC. Moreover, the P-MCA had the significantly highest (p < 0.05) acceptance score for all sensory attributes in both raw form and as a pizza topping. In conclusion, the P-MCA showed superior performance in terms of functionality and sensory acceptance.